Pengembangan Website Ketersediaan dan Peminjaman Barang Prodi MPLM ”BaPro ( Barang Prodi ) MPLM” - Siti Sahara; Bintang Arya Mahasyahputra; Putri Wulandari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to design and develop a website related to the availability and borrowing of goods at the campus Prodi. This research was conducted by means of research and development. which consists of five stages, namely 1) analysis, 2) design, 3) development, 4) implementation and 5) evaluation. At the analysis stage, an analysis is carried out related to the needs of the management system for the availability and borrowing of study programme goods and the collection of information that can be used as material for making media products, design (design) this stage is carried out to facilitate researchers in designing a website for managing the availability of goods that will be made. The development stage (Development) at this stage of application development is the stage of realising what is designed in the design stage in order to become a website product for the availability and loan of goods. Implementation stage (Implement) website products that have been made are implemented and tested on students of the Port Management and Maritime Logistics study programme. Evaluation is a process carried out to provide value to learning programmes. According to the validation results of learning design experts, media experts, and teacher validation as material experts, the results of development research in the form of a website for the availability and loan of goods show very positive results and are suitable for use by students.